CRISPR-mediated genome editing of wheat for enhancing disease resistance - Waites, Joshua O.; Achary, Mohan Murali; David, Easter S.; Hearne, Sarah; Bandyopadhyay, Anindya (Frontiers Media, 2025)
Wheat is cultivated across diverse global environments, and its productivity is significantly impacted by various biotic stresses, most importantly but not limited to rust diseases, Fusarium head blight, wheat blast, and powdery mildew. The genetic diversity of modern cultivars has been eroded by domestication and selection, increasing their vulnerability to biotic stress due to uniformity. The rapid spread of new highly virulent and aggressive pathogen strains has exacerbated this situation. Three strategies can be used for enhancing disease resistance through genome editing: introducing resistance (R) gene-mediated resistance, engineering nucleotide-binding leucine-rich repeat receptors (NLRs), and manipulating susceptibility (S) genes to stop pathogens from exploiting these factors to support infection. Utilizing R gene-mediated resistance is the most common strategy for traditional breeding approaches, but the continuous evolution of pathogen effectors can eventually overcome this resistance. Moreover, modifying S genes can confer pleiotropic effects that hinder their use in agriculture. Enhancing disease resistance is paramount for sustainable wheat production and food security, and new tools and strategies are of great importance to the research community. The application of CRISPR-based genome editing provides promise to improve disease resistance, allowing access to a broader range of solutions beyond random mutagenesis or intraspecific variation, unlocking new ways to improve crops, and speeding up resistance breeding. Here, we first summarize the major disease resistance strategies in the context of important wheat diseases and their limitations. Next, we turn our attention to the powerful applications of genome editing technology in creating new wheat varieties against important wheat diseases.